Increase in the mitotic recombination frequency in Drosophila melanogaster by magnetic field exposure and its suppression by vitamin E supplement. - Koana, T.; Okada, M.O.; Ikehata, M.; Nakagawa, M. (Mutation Research, 1997)
In order to estimate possible mutagenic and/or carcinogenic activity of electromagnetic fields, wing spot tests were performed in Drosophila melanogaster. A DNA repair defective mutation mei-41D5 was introduced into the conventional mwh/flr test system to enhance mutant spot frequency. Third instar larvae were exposed to a 5-Tesla static magnetic field for 24 h, and after molting, wings were examined under a microscope to detect hair spots with mutant morphology. The exposure caused a statistically significant enhancement of somatic recombination compared with the unexposed control. This enhancement was suppressed to the control level by supplement of vitamin E, a non-specific antioxidant. It is inferred that the magnetic field enhanced the genotoxic effect of spontaneously produced free radicals, possibly by affecting the lifetime of the radicals. Enhancement of non-disjunction, terminal deletions and gene mutations were not detected.